2019
DOI: 10.17977/um002v11i22019p186
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Influencing Export Quantity for Indonesian and Philippine Coconut Oil

Abstract: The coconut oil as main product of coconut is not competitive anymore compared to palm oil. Indonesia and Philippines are two top producers of coconut. This paper studies whether the price of coconut oil, the price of crude palm oil, the price of virgin olive oil, and gross domestic product influence the quantity export for Indonesian and Philippines coconut oil. Using multiple linear regression, the results indicate that in the Philippines the variables used in the study (price of coconut oil, price of crude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…Turukay observed soybean oil, [31] elucidating the identical factors, sharpened by the soybean oil price and RCA index (which revealed a comparative advantage) as the influential determinants. According to Tanago et al [32], the factors could vary across countries; they found several distinct outcomes between Indonesian and Philippine coconut oil exports, such as the nation's GDP leading to higher Indonesian export values; however, it had no impact on the rival country. Moreover, the finding by Rosyidi [33] indicates that the partner-country GDP could lead to positive export increases in Indonesian agricultural commodities, along with their commodity prices; however, the exchange rate has an adverse impact.…”
Section: Determinant Of Coconut Oil Export Marketsmentioning
confidence: 99%
See 2 more Smart Citations
“…Turukay observed soybean oil, [31] elucidating the identical factors, sharpened by the soybean oil price and RCA index (which revealed a comparative advantage) as the influential determinants. According to Tanago et al [32], the factors could vary across countries; they found several distinct outcomes between Indonesian and Philippine coconut oil exports, such as the nation's GDP leading to higher Indonesian export values; however, it had no impact on the rival country. Moreover, the finding by Rosyidi [33] indicates that the partner-country GDP could lead to positive export increases in Indonesian agricultural commodities, along with their commodity prices; however, the exchange rate has an adverse impact.…”
Section: Determinant Of Coconut Oil Export Marketsmentioning
confidence: 99%
“…Indonesian Real GDP The real GDP value of Indonesia on an annual basis World Economics [37] (+) [30,32] 5.…”
Section: Coconut Oil Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selain pasar China, pasar Amerika Serikat dan Korea Selatan juga menjadi tujuan utama dari ekspor CCO Indonesia yang mencapai 65% dari total ekspor kelapa Indonesia (Purba et al, 2021). GDP Indonesia juga turut memberi pengaruh positif pada peningkatan ekspor CCO Indonesia (Tanago and Kaluge, 2019).…”
Section: Pendahuluanunclassified